Effect of lifelong sucrose consumption at human-relevant levels on food intake and body composition of C57BL/6N mice - Yan, Ruolin; Choi, Vivian Wai Wan; Hartono, Tania; Tse, Iris Mei Ying; Tse, Margaret Chui Ling; Zhou, Yunpeng; Xu, Jinfeng; Sit, Wai Hung; Wan, Jennifer Man Fan; Li, Edmund Tsz Shing; Chan, Chi Bun; Louie, Jimmy Chun Yu (Frontiers in Nutrition, 2022)
Introduction: Controversies surround the issue of whether chronic consumption of a high-sugar diet is detrimental to health or not. This study investigates whether lifelong consumption of a higher sucrose diet will induce overeating, and obesity, and cause metabolic dysfunctions such as hyperglycaemia and dyslipidaemia in C57BL/6N mice, compared to a lower sucrose diet. Methods: Male C57BL/6N mice at 3 weeks of age were randomized into consuming a diet with 25%kcal or 10%kcal from sucrose for the rest of their lives. Bodyweight, food and water intake, fasting blood glucose, insulin, and lipid levels were measured at regular intervals. At the end of the study, organs and tissues were collected and gene expression was measured. Results: There was no discernible difference in the impact on food intake, body composition, glucose and lipid homeostasis, liver triglyceride content, life expectancy, as well as gene expression related to intermediary metabolism between mice fed a diet with 10%kcal vs. 25%kcal as sucrose over their lifespan. We also showed that switching from a 25%kcal diet to a 10%kcal diet at different life stages, or vice versa, did not appear to affect these outcomes of interest. Conclusions: Our unorthodox findings disagreed with the popular belief that higher sugar consumption is detrimental to health, which should be confirmed in future studies.